2014
DOI: 10.3310/phr02040
|View full text |Cite
|
Sign up to set email alerts
|

Does the Royal Horticultural Society Campaign for School Gardening increase intake of fruit and vegetables in children? Results from two randomised controlled trials

Abstract: BackgroundChildren’s fruit and vegetable intake in the UK is low. Changing intake is challenging. Gardening in schools might be a vehicle for facilitating fruit and vegetable intake.ObjectivesTo undertake the first clustered randomised controlled trials (RCTs) of a gardening intervention. To evaluate the impact of a school gardening programme, the Royal Horticultural Society (RHS) Campaign for School Gardening, on children’s fruit and vegetable intake.MethodsPrimary school children aged 8–11 years from eight L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 117 publications
(251 reference statements)
0
22
1
Order By: Relevance
“…In high-income countries, school gardens are established mostly for academic, behavioural, nutritional, recreational, environmental and social purposes (Blair 2009;Skelly and Bradley 2007;Ozer 2007;Ratcliffe et al 2011;Christian, Evans, and Cade 2014). In low-income countries, improving nutrition and transferring agricultural skills are the main goals for school gardens (FAO 2005;Kommu 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In high-income countries, school gardens are established mostly for academic, behavioural, nutritional, recreational, environmental and social purposes (Blair 2009;Skelly and Bradley 2007;Ozer 2007;Ratcliffe et al 2011;Christian, Evans, and Cade 2014). In low-income countries, improving nutrition and transferring agricultural skills are the main goals for school gardens (FAO 2005;Kommu 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Others studies did find significant improvements in children's vegetable consumption (McAleese and Rankin 2007;Parmer et al 2009;Wang et al 2010). However, for a study in the United Kingdom, Christian et al (2014) found no evidence that the average school garden program improved children's knowledge, attitudes, or fruit and vegetable intake.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, this is the first application of a randomized controlled trial to the evaluation of school gardens in a developing country. Previously published studies have applied such methods to the evaluation of school gardens in the United Kingdom (Hutchinson et al 2015;Christian et al 2012;Christian et al 2014;Evans et al 2013).…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, gardening workshops have become very popular. In their article, Christian et al (2014) highlight the obtained results of the Campaign for School Gardening (RHS -Royal Horticultural Society), emphasizing the increase in fruit and vegetable consumption among children [9]. Consequently, different measurements were proposed to be integrated in order to obtain a sustainable gardening experience:…”
Section: School-based Green Experience -Physical and Mental Activity mentioning
confidence: 99%